2021
DOI: 10.3390/antiox10060859
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Oxidative and Anti-Neuroinflammatory Effects of Sargassum horneri by Heme Oxygenase-1 Induction in BV2 and HT22 Cells

Abstract: Sargassum horneri is used as a traditional medicinal agent and exhibits various pharmacological effects. In this study, we found that the 70% EtOH extract contained 34.37 ± 0.75 μg/mg fucosterol. We tested the antioxidant activities of the 70% EtOH extracts and their fractions. The CH2Cl2-soluble fraction showed the strongest DPPH and ABTS radical scavenging activities. Next, we evaluated the anti-neuroinflammatory effects of S. horneri on lipopolysaccharide (LPS)-stimulated BV2 cells. Pretreatment with the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 51 publications
(68 reference statements)
0
27
0
1
Order By: Relevance
“…Among the various physiological processes, the chronic inflammatory response is an important process that can lead to various chronic diseases. Factors associated with inflammatory responses include NO, PGE 2 , and inflammatory cytokines, which are regulated by a variety of inflammatory modulators [ 27 ]. NO, the representative inflammatory mediator, acts as a trigger causing ROS production that lead to cell damage and cell death [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the various physiological processes, the chronic inflammatory response is an important process that can lead to various chronic diseases. Factors associated with inflammatory responses include NO, PGE 2 , and inflammatory cytokines, which are regulated by a variety of inflammatory modulators [ 27 ]. NO, the representative inflammatory mediator, acts as a trigger causing ROS production that lead to cell damage and cell death [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result supported the findings that S. horneri effectively reduced the NO and ROS production in previous studies [ 14 , 15 , 17 ]. iNOS and COX-2 are key inflammatory mediators that influence the production of NO and PGE 2 [ 27 ]. According to the data shown in Figure 2 , SC effectively reduced the expression of COX-2 protein, which induces PGE 2 production, and the expression of iNOS protein, which induces NO production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed Western blotting to investigate whether com-pounds 3 and 4 increase the expression level of HO-1, wherein the well-known HO-1 inducer cobalt protoporphyrin (CoPP) was used as a positive control increasing HO-1 protein expression. [30]. The results revealed that compounds 3 and 4 also upregulated the expression of HO-1 (Figure 7).…”
Section: Effects Of Compounds 3 and 4 On The Nrf2/ho-1 Pathway In Bv2...mentioning
confidence: 85%
“…Fucosterol from S. horneri showed strong free radical scavenging activities in DPPH and 2,2 azino-bis3-ethylbenthiazoline-6-sulfonic acid (ABTS) assays. In addition, fucosterol attenuated the oxidative actions in HT22 and BV2 cells by enhancing the HO-1 and Nrf2 levels in the cytoplasm and nucleus, respectively [ 74 ]. Similarly, fucosterol from P. boryana , a brown seaweed, significantly upregulated the antioxidant proteins such as Nrf2, and HO-1 and downregulated the Kelch-like ECH-associated protein-1 (Keap1) in the RAW 264.7 macrophage cell line induced with PM [ 67 ], in addition to anti-inflammatory activity.…”
Section: Health Benefits and Biomedical Applications Of Phytosterolsmentioning
confidence: 99%